Characterization of degradation products of activated diethanolamine and methyldiethanolamine during carbon dioxide absorption and desorption processes / Md. Sakinul Islam - Md. Sakinul, Islam (2012)
Degradation studies of activated Diethanolamine (DEA) and Methyldiethanolamine (MDEA) induced by carbon dioxide were conducted in jacketed glass reactor under absorber and stripper conditions at atmospheric pressure. Piperazine (PZ) is used as an activator in this system. There are eighteen amines and activated amine samples studied. Pure carbon dioxide was bubbled through the reactor till saturation. The concentration of amine and activator used ranging from 2M to 4M and 1M to 2M respectively. On the other hand activated amine concentrations ranged from 4M to 11M. Six generic cycles were conducted for each run during the degradation experiments. Each cycle configured with the absorption and desorption of carbon dioxide at 55 ˚C and 100 ˚C respectively. Samples were collected after a predetermined experimental time and analyzed by various chromatographic methods to identify degradation products. The degradation products were identified using ion chromatography (IC), high performance liquid chromatography (HPLC)-UV detection and gas chromatography mass spectroscopy (GC/MS). In the IC analysis three different columns were used for Anion, Cation and Ion exclusion systems these are Metrosep A Supp 5 150/4.0, Metrosep C Supp 4 150/4.0 and Metrosep Organic Acids respectively. The supelco HPLC column was used to identify polar degradation products of amine sample. In the GC-MS chromatographic analysis HPINNOWAX (30 m × 0.250 mm × 0.25μm) column was used. The major identified degradation products in IC analysis are nitrate, nitrite, acetate, phosphate and ammonium. In HPLC analysis the most common degradation products are found formamide, 2-(2- aminoethoxy)ethanol, Diethylenetriamine, Ethyl 1-piperazinecarboxylate, N-(2-Hydroxyethyl) ethylenediamine, Triethanolamine, 2-Methoxyethanol, Ethylene glycol, 1,4- Dimethylpiperazine and 1-(2-Aminoethyl) piperazine. GC-MS is particularly conducted for five alkanolamine samples which are DO2PZ2M, D05DEA4M, D10DEA7MPZ2M, D13MDEA4M and D18MDEA7MPZ2M. Five degradation products are identified for DO2PZ2M and these are Formamide, Ethylenediamine, N-formylpiperazine, Fomic acid and Imidazole. D05DEA4M degraded sample shows ten degradation products these are Formamide, N-(hydroxyethy1) ethylenediamine, Oxazolidone, 2-(2-aminoethoxy) ethanol, 2- amino-2-methyl-1-propanol, N,N-bis(hydroxyethy1)- ethylenediamine, Ethylurea, 2- methylaminoethanol, ethanol and acetone. Activated DEA sample D10DEA7MPZ2M shows twelve DGPs these are Formamide, 1,4-Bis(2-hydroxyethyl)piperazine, Oxazolidone, 1,4- Dimethylpiperazine, N,N-bis(hydroxyethy1)ethylenediamine, 2-dimethylaminoethanol, 1-(2- Aminoethyl)piperazine, Ethyl-1-piperazinecarboxylate, Acetic acid, Glycolic acid, Ethyl urea and Acetone. Inactivated MDEA samples D13MDEA4M was analyzed and eleven degradation products are found which are 1, 4-Bis (2-hydroxyethyl)-piperazine, Bis-(2-hydroxypropyl) amine, Oxazolidone, 2-(2-aminoethoxy)ethanol, 2-Amino-2-methyl-1-propanol, 2- dimethylaminoethanol, Ethylurea, Glycolic acid, Acetaldehyde, Ethanol and Acetic acid. Similarly eight degradation products are found for D18MDEA7MPZ2M sample which are 1- Methyl piperazine, 1, 4-Bis(2-hydroxyethyl)piperazine, Bis(2-hydroxypropyl) amine, N, Ndimethyl piperazine, 2-Amino-2-methyl-1-propanol, 2-dimethylaminoethanol, 1-(2- aminoethyl) piperazine and ethanol. In addition two physical properties density and viscosity of eighteen activated and inactivated amine samples are measured at 30 ˚C, 55 ˚C and 100 ˚C and it was found that the both physical properties decreased with increasing temperature. However, in case of increasing concentration it is significantly increases the density and viscosity of both activated and inactivated amine solutions. Keywords: Degradation, activated diethanolamine, activated methyldiethanolamine, absorption, stripping, desorption.